2018
DOI: 10.1021/acs.langmuir.8b01569
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cleaning Interfaces of Polydimethylsiloxane Grafted with pH-Responsive Zwitterionic Copolymers

Abstract: Self-cleaning surfaces allow the reversible attachment and detachment of microorganisms which show great promise in regards to their reusability as smart biomaterials. However, a widely used biomaterial such as polydimethylsiloxane (PDMS) suffers from high biofouling activity and hydrophobic recovery that results in decreased efficiency and stability. A current challenge is to modify and fabricate self-cleaning PDMS surfaces by incorporating antifouling and pH-sensitive properties. To address this, we synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…Therefore, the larger size of the Au 0 core in the Au@PMo nanostructures is attributed to the superior redox activity of the PMo cluster compared to the PW analogue. 34 The preferential synthesis on the PDMS surface is supported by a nucleation-growing mechanism in which the roughness, i.e., 95 nm, and ζ-potential 35 of the PDMS surface promote the heterogeneous nucleation of Au 0 seeds (Figure 2d). Such nuclei grow further in the presence of POMs and remain attached to the microfluidic wall via electrostatic interactions due to the reaction pH is below the isoelectric point of PDMS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the larger size of the Au 0 core in the Au@PMo nanostructures is attributed to the superior redox activity of the PMo cluster compared to the PW analogue. 34 The preferential synthesis on the PDMS surface is supported by a nucleation-growing mechanism in which the roughness, i.e., 95 nm, and ζ-potential 35 of the PDMS surface promote the heterogeneous nucleation of Au 0 seeds (Figure 2d). Such nuclei grow further in the presence of POMs and remain attached to the microfluidic wall via electrostatic interactions due to the reaction pH is below the isoelectric point of PDMS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[10][11][12] Hence, zwitterion-containing polymers are usually relatively inert and promising ultra-low-fouling materials. [13][14][15][16] Incorporated in different ways, e.g. in polymer brushes, or photo-crosslinkable polymer films, their low adsorption properties have been demonstrated against proteins, [17][18][19] bacteria, 10,20,21 and marine organisms.…”
Section: Introductionmentioning
confidence: 99%
“…27 Moreover, the orientation of the anchoring of the zwitterionic moiety to the matrix has been discussed as an additional parameter. 13,15,[28][29][30][31] We recently revealed that the orientation in which sulfobetaines are anchored to the polymer backbone can indeed have a significant impact on the resistance of such polyzwitterion films against non-specific adsorption of proteins. 19,28 Films of polysulfobetaines with a linearly anchored dipole orientation performed more effectively in antifouling coatings compared to a novel y-shaped analogue, in which both ionic groups had the same distance to the polymeric backbone.…”
Section: Introductionmentioning
confidence: 99%
“…By condensing Si═OH groups with a cross‐linker, strong polymer networks are formed . PDMS has been frequently used in hydrophobic surface preparation in recent years but has never been applied to the catalyst layer of PEM fuel cell. PDMS is a polymer with high chemical resistance and hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%